Konsep Diversi dalam Pertanggungjawaban Pidana Anak Pelaku Kecelakaan Lalu Lintas yang Mengakibatkan Hilangnya Nyawa Orang Lain - Dewi Nur Widayanti; Tegar Harbriyana Putra; Dwi Imroatus Sholikah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Traffic accidents involving juveniles that result in the death of another person have become an important issue in the juvenile criminal justice system. These cases raise questions regarding the limits of juvenile criminal liability and the effectiveness of diversion as an alternative to formal criminal proceedings. This study aims to examine the application of the ultimum remedium principle in the judicial considerations of Boyolali District Court Decision Number 1/Pid.Sus-Anak/2023/PN Byl and to analyze the factors influencing the implementation of diversion. This study employed an empirical juridical method using statutory, case, and empirical approaches. Data were collected through interviews and library research on primary, secondary, and tertiary legal materials, and were analyzed qualitatively. The findings show that the judge applied criminal punishment as a last resort after diversion had been attempted in accordance with applicable legal provisions. However, diversion failed because of conflicting interests between the offender and the victim’s family, the severity of the consequences, and considerations of justice. The study concludes that successful diversion requires not only adequate legal provisions but also the willingness of the parties to achieve restorative justice while protecting children's rights, ensuring victims' interests, and maintaining legal certainty.